Portrait of Roosevelt Junior High School Drum Corp - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait of teenaged boys and girls lined up in front of Roosevelt Junior High School in San Jose. The students pose with drums and trumpets.Two majorettes with batons stand in the center back row with the drum major between them. Two students at the center of the front row hold up a banner that reads "Roosevelt".